Combining Trinexapac‐Ethyl with a Soil Surfactant Reduces Bermudagrass Irrigation Requirements. (1st November 2018) - Serena, Matteo; Sportelli, Mino; Sevostianova, Elena; Sallenave, Rossana; Leinauer, Bernhard
Abstract : Core Ideas: We describe the use of a plant growth regulator and a soil surfactant for water conservation. We investigated whether the beneficial effects of a surfactant and a plant growth regulator on drought stressed bermudagrass were enhanced when applied in combination versus individually. We investigated if both products affect soil moisture under reduced irrigation. Soil surfactants and plant growth regulators (PGR) have shown potential to lower irrigation requirements and increase turfgrass quality under drought conditions. A study was conducted from 2014 to 2016 to investigate the soil surfactant Revolution, (modified methyl capped block copolymer [Aquatrols, Paulsboro, NJ]), or the plant growth regulator 'PrimoMaxx' (A.I. trinexapac‐ethyl [4‐(cyclopropylhydroxymethylene)‐3, 5‐dioxocyclohexanecarboxylic acid]) (Syngenta, Basel, Switzerland), or a combination of both on percent green coverage, turfgrass color, quality, soil volumetric water content (VWC) and uniformity on Princess 77 bermudagrass ( Cynodon dactylon L.) grown on a loamy sand (mixed, thermic Typic Torripsamments) and irrigated at either 80%, 65%, or 50% of reference evapotranspiration for short grass (ETOS ). With the exception of plots irrigated at 50% ETos in 2015, bermudagrass receiving trinexapac‐ethyl (TE) either in combination with Revolution or alone exhibited darker green color when compared to untreated controls at all irrigation levels throughout the research period. At 50% ETos, plots treated with any of the three chemical treatments had greater quality (with 1 = worst, 9 = best) than control plots from July to September, with quality ratings of 6 or greater from June to August. Whereas VWC was not consistently enhanced by all treatment combinations, applications of Revolution, TE, and the combination of both resulted in increased VWC uniformity and greater irrigation use efficiency. Our results suggest that by using a surfactant, a PGR, or both, bermudagrass quality can be maintained with 15 to 30% less irrigation water than the optimal rate (80% ETos) without a reduction in color or quality.